1991
DOI: 10.1192/bjp.159.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive Slowness Revisited

Abstract: Of 665 patients referred between 1969 and 1984 for behavioural treatment of obsessive-compulsive disorder, 22 had marked slowness not due to washing, which was secondary to mental or overt rituals or ruminations. Over 90% of the slowness cases were male, and over a quarter had pre-natal or delivery problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Women are more prone to contamination obsessions, 22 usually associated with cleaning rituals; 6,19,23,24 whereas sexual obsessions are more common among men. 19,22,23,35 Several studies combine rates of sexual and religious symptoms, which are more frequent in males. 6,24,36 Results are inconclusive regarding aggressive obsessions, with studies showing varying predominance between genders.…”
Section: Phenotypical Studiesmentioning
confidence: 99%
“…Women are more prone to contamination obsessions, 22 usually associated with cleaning rituals; 6,19,23,24 whereas sexual obsessions are more common among men. 19,22,23,35 Several studies combine rates of sexual and religious symptoms, which are more frequent in males. 6,24,36 Results are inconclusive regarding aggressive obsessions, with studies showing varying predominance between genders.…”
Section: Phenotypical Studiesmentioning
confidence: 99%
“…It is characterized by prominent debilitating slowness especially in self care, behavior, extreme meticulousness, absence of an increase in anxiety or discomfort either before or following the behavior (or with initiation of treatment) and relative lack of resistance. Subsequently, others published case reports or case series (4-10 patients) that detailed features of this syndrome (Bennun, 1980;Bilsubury and Morley, 1979;Clark et al, 1982;Hymas et al, 1991;Ratnasuriya et al, 1991;Takeuchi et al, 1997). Veale in 1993 challenged the proposed syndrome by pointing out that slowness in most of these patients is secondary to behavioral or mental rituals, aimed at suppressing or neutralizing obsessional thoughts.…”
Section: Introductionmentioning
confidence: 93%
“…In three subsequent reports, investigators debated whether or not obsessional slowness seemed to be a severe form of OCD or better explained as a primary problem. Ratnasuriya et al. (1991) reported that all of the 22 cases of slowness they found in a retrospective chart review displayed obsessive and compulsive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…While obsessional slowness is thought to be exceedingly rare in the general population (Ratnasuriya et al. 1991), some have the impression it occurs more frequently in people with DS (A. D. Hurley, personal communication).…”
Section: Introductionmentioning
confidence: 99%